العوامل المؤثرة في تذوق الأدب العربي وفهمه عند المتعلمين غير الناطقين بالعربية - Usof, Abduloh; Anuar, Muhammad Afiq (SIBAWAYH Arabic Language and Education, 2025)
الملخص يُعَدّ الأدب العربي من أبرز الأدوات التي يمكن توظيفها في تعليم اللغة العربية للناطقين بغيرها، إذ إنه يجمع بين الجانب اللغوي والجمالي والثقافي، ويمنح المتعلم فرصة للاطلاع على روح الثقافة العربية وقيمها الحضارية. فالنص الأدبي ليس مجرد بناء لغوي جامد، بل هو نتاج فكري وجمالي يعكس تجربة إنسانية وثقافية عميقة. ومن ثمّ فإن تدريسه يسهم في تعميق المهارات اللغوية، وتنمية القدرة على التفكير النقدي والإبداعي، وتعزيز التفاعل مع الثقافة العربية في أبعادها المختلفة. غير أن الواقع يشير إلى أن المتعلمين غير الناطقين بالعربية يواجهون صعوبات جمّة عند التعامل مع النصوص الأدبية، تتمثل في عوامل لغوية مثل صعوبة المفردات والتراكيب البلاغية المعقدة، وعوامل ثقافية تتمثل في غياب المعرفة بالرموز الدينية والاجتماعية والتاريخية، وعوامل تربوية تتمثل في اقتصار طرق التدريس على التلقين والترجمة، فضلًا عن عوامل نفسية تتعلق بالدافعية والاتجاهات نحو الأدب. تهدف هذه الدراسة إلى استكشاف أبرز هذه العوامل المؤثرة في تذوق الأدب العربي وفهمه عند المتعلمين غير الناطقين بالعربية، وتحليل انعكاساتها على عملية التلقي، ثم اقتراح آليات نظرية وتربوية للتغلب عليها. وقد اعتمد البحث على المنهج المكتبي الاستقرائي من خلال تحليل الدراسات السابقة ذات الصلة واستقراء نتائجها. وتوصّلت الدراسة إلى أن تحقيق التذوق الأدبي يتطلب معالجة متكاملة تشمل التبسيط اللغوي التدريجي، وتقديم شروح ثقافية ملائمة، واعتماد طرائق تدريس تفاعلية حديثة، إضافة إلى تعزيز دافعية الطلاب واتجاهاتهم الإيجابية نحو الأدب العربي، بما يضمن توظيف الأدب كأداة فعّالة في تعليم اللغة وتعميق الفهم الثقافي. الكلمات المفتاحية: الأدب العربي، تعليم العربية للناطقين بغيرها، التذوق الأدبي، العوامل المؤثرة، الثقافة Abstract Arabic literature represents one of the most influential tools in teaching Arabic as a foreign language, as it combines linguistic, aesthetic, and cultural dimensions, offering learners a unique opportunity to access the spirit of Arab civilization and its values. Literary texts are not merely linguistic constructions but intellectual and artistic products that reflect profound human and cultural experiences. Teaching literature therefore contributes to enhancing linguistic competence, developing critical and creative thinking, and fostering intercultural understanding. However, non-native learners often encounter multiple obstacles when dealing with Arabic literary texts. These challenges include linguistic difficulties, such as complex vocabulary and rhetorical structures; cultural barriers, such as the lack of familiarity with religious, historical, and social references; pedagogical limitations, where teaching methods rely heavily on rote explanation or direct translation; and psychological issues, including low motivation and negative attitudes toward literature. This study seeks to explore the key factors influencing the comprehension and appreciation of Arabic literature among non-native learners, to analyze their impact on the reception of texts, and to propose theoretical and pedagogical strategies to overcome these challenges. The research adopts an inductive library-based method, analyzing previous studies and synthesizing their findings to develop a comprehensive framework. The study concludes that literary appreciation requires an integrated approach that includes gradual linguistic simplification, providing appropriate cultural explanations, adopting interactive and modern teaching strategies, and enhancing learners’ motivation and positive attitudes toward Arabic literature. In doing so, literature can be effectively employed not only as a tool for language acquisition but also as a means of deepening cultural understanding and fostering global dialogue. Keywords: Arabic literature, teaching Arabic as a foreign language, literary appreciation, influencing factors, culture.